Vous êtes sur la page 1sur 11

Copyright Rene Barrientos Page 1

MAP2302 Lecture 4 2010-3


LINEAR DIFFERENTIAL EQUATIONS
Integrating Factors
A first order equation that can be written in the form
a
1
(x)y' +a

(x)y = g(x) (1)


where o
0
(x), o
1
(x), anu g(x) are arbitrary functions of x is called a first order linear equation and equation (1) is
its general form. For example, the equation
y
i
= -yx
is a first order linear equation because it can be written as
xy
i
+y = u
which has the form of equation (1) with a
1
(x) = x, a

(x) = 1, and g(x) = .


Let us first consider the simplest possible case: o
1
(x) = u, o
0
(x) = u on some interval I. In this case (1) is
separable and reduces to the familiar y
i
= (x):
Jy
Jx
=
g(x)
o
1
(x)

which we can easily be solved by integration:
y(x) = _
g(x)
a
1
(x)
dx +c
where c is an arbitrary constant. Needless to say, these are the rare cases for in general o
0
(x) = u. We will now
show that under fairly general assumptions equation (1) can be solved by introducing an integrating factor. Our
first step is to write the equation in its standard form, which is obtained by dividing its terms by the leading
coefficient o
1
(x):
y' +p(x)y = (x) (2)
where p(x) = o
0
(x)o
1
(x) and (x) = g(x)o
1
(x). From this point forward, we will always assume a linear
equation has been expressed in its standard form.
Now imagine that we are able to find a function (x) such that equation (2) can rewritten as
d
dx
((x) y(x)) = (x) (x)
Then integration leads to a solution:
p(x)y(x) = _p(x)(x) Jx +c
or
y(x) =
1
p(x)
_p(x)(x) Jx +
c
p(x)

where c is an arbitrary constant. Any function p(x) which allows us to do this is called an integrating factor of
equation (2) and our aim now is to obtain it.
So let us multiply equation (2) by the yet undetermined factor p(x):
p(x)y' +p(x)p(x)y = p(x)(x)
In order for an integration factor to have the desired effect, it must convert the expression p(x)y' +p(x)p(x)y
into
d
dx
|(x) y]. In other words, the function p(x) must be such that
p(x)y
i
+p(x)p(x)y =
J
Jx
(py)
Using the product rule on the right-hand side,
Copyright Rene Barrientos Page 2

py +p p(x)y = py +py
Cancelling py,
p p(x)y = py
Cancelling y and separating variables,
Jp
p
= p(x)Jx; y = u
Solving for p
ln|p| = _p(x) Jx +c
= _Ae
]p(x)dx

This gives us a family of functions that have the desired property, but we only need one. Setting A = 1 and
dropping the _:


When ]p(x) Jx is a complicated expression we use the following alternate notation instead:
= exp__p(x) dx]
where exp(a) e
a
.
The procedure used to solve linear equations using integrating factors can be summarized as follows:















In practice it is not a good idea to memorize the formula in step (4) because it is not obvious and easy to make
mistakes with. It is better to remember the how to obtain the integrating factor and go through the steps.
Let us first compute some integrating factors:

Differential Equation Standard Form p(x) (x)
xy
i
+2y = 1 y
i
+
2
x
y =
1
x

2
x
c
](2x)dx
= x
2

y
i
+2xy = x
3
y
i
+2xy = x
3
2x
c
](2x)dx
= e
x
2

Sy
i
-x
3
y = x +x
2

y
i
-
x
3
S
y =
x +x
2
S
-
x
3
S

c
](-x
3
3)dx
= e
-
x
4
12



= e
]p(x)dx

dy
dx
+p(x)y = q(x)
(x)y +(x)p(x)y = (x)q(x)
d
dx
|e
]p(x)dx
y] = e
]p(x)dx
q(x)
(x)y = _(x)q(x)dx +c
y(x) =
1
(x)
__(x)q(x)dx +c]
To solve
(1) multiply the differential equation by (x) = e
]p(x)dx

(2) Then by the way was defined we have
(3) Integrate:
(4) Solving for y:
Copyright Rene Barrientos Page 3

Remarks:
1) It is very important to remember that the differential equation is in standard form.
2) by construction, the integrating factor converts the left-hand side of (2) into
d
dx
(tntegrattng Iatur dependent vartable)
Caution: if other variables are used besides the usual x and y, make sure that you use them. Do not bring into the problem
variables that were not there to begin with.
I initial value problems can be solved via the definite integral instead:
d
dx
((x) y) = (x) q(x) = _
d
dx
((x) y(x))
x
x

dx = _(x) q(x)dx
x
x


Thus,
(x) y(x) -(x

) y(x

) = _(x) q(x)dx
x
x


or




Example 2 Solve y
i
= 2x -y
Solution
1) Write the differential equation in standard form,
y
i
+y = 2x
2) p(x) = 1 so an integrating factor is p = c
]1dx
= c
x
.
3) multiplying by the integrating factor:
c
x
y
i
+c
x
y = 2xc
x

or
J
Jx
(c
x
y) = 2xc
x

4) Integrating,
c
x
y = 2_xc
x
Jx +k
Integration by parts tells us that ]xc
x
Jx = xc
x
-c
x
. Thus,
c
x
y = 2(xc
x
-c
x
) +k

Solving for y:
y(x) = 2x -2 +ke
-x

The figure below corresponds to the slope field of this differential equation.
y(x) =
1
(x)
_(x

) y

+ _(x) q(x)dx
x
x

_

Copyright Rene Barrientos Page 4


Here are some of the members of the family of solutions:


Compare this graph with the slope field above. The separatrix y = 2x -2, shown as a dotted red line, is a solution of
the equation; It corresponds to k = u.
Example 3 Solve xy
i
+2y = 1
Solution
1) Write the equation in standard form:
y +
2
x
y =
1
x

The coefficient of y is
2
x
: p(x) =
2
x

2) Find the integrating factor
(x) = c
](2x)dx
= c
2In|x|
= x
2

3) Multiplying the equation is step 1) by p(x)
x
2
y +x
2
2
x
y = x
2
1
x
|multiplying by p]
x
2
y +2xy = x |simplifying]

J
Jx
(x
2
y) = x |iewiting]
-2 -1 0 1 2
-2
-1
0
1
2
-3 -2 -1 1 2 3
-3
-2
-1
1
2
3
y
i
= 2x -y
Field corresponding to
y = 2x - 2
Copyright Rene Barrientos Page 5

[ verify that
d
dx
(x
2
y) = x
2
y
i
+2xy ]
4) We are ready to integrate:
x
2
y = _x Jx +c =
x
2
2
+c
Solving for y:
y =
1
2
+
c
x
2

Done!
A quick substitution into the original equation tells us that x [
1
2
+
c
x
2

i
+2[
1
2
+
c
x
2
= 1
Once again, the hardest thing here is to evaluate the last integral. There will be times when this is very
difficult and we might have to use a computer, tables, or even leave the answer in terms of an integral.
Example 4 Solve y
i
+2xy = x
3

Solution
This equation is already in standard form, and we found that p = c
x
2
is an integrating factor.
Multiplying the equation by this factor will make the left hand side equal to the derivative of the
integrating factor times the dependent variable:
c
x
2
y
i
+c
x
2
2xy = c
x
2
x
3

J
Jx
(c
x
2
y) = c
x
2
x
3

Integrating:
c
x
2
y = _x
3
c
x
2
Jx +c
To evaluate this integral, we can use a table or use integration by parts. Using the latter,
_x
3
c
x
2
Jx =
1
2
_x
2
c
x
2
2x Jx
let u = x
2
anu du = e
x
2
2xdx
Then
du = 2xdx u = e
x
2

Thus,
_x
3
c
x
2
Jx =
1
2
_x
2
c
x
2
2x Jx =
1
2
_x
2
c
x
2
-_c
x
2
2xJx ]
=
1
2
(x
2
c
x
2
-c
x
2
)
Finally we have our solution:
c
x
2
y =
1
2
(x
2
c
x
2
-c
x
2
) +c
Solving for y
y =
1
2
(x
2
-1) +ce
-x
2

Example 5 Solve y
i
= 1 +x +y +xy, y(u) = u
Solution
First write the equation in standard form:
y
i
-(x +1)y = x +1, y(u) = u
An integrating factor of this equations is
p = c
-](x+1)dx
= c
-_
x
2
2
+x]

Copyright Rene Barrientos Page 6

It is more convenient to write = exp[-
x
2
2
-x because of the complexity of the argument -
x
2
2
-x.
Thus,
J
Jx
_exp_-
x
2
2
-x_y_ = exp_-
x
2
2
-x_(x +1)
Integrating,
exp _-
x
2
2
-x_y = _exp_-
x
2
2
-x_(x +1) Jx +c
Let u = -
x
2
2
-x. Then du = (-x -1)dx = -(x +1)dx so the integral is straightforward:
exp _-
x
2
2
-x_y = -_exp(u) Ju +c
or
exp_-
x
2
2
-x_y = -exp _-
x
2
2
-x_ +c
Solving for y:
y(x) = -1 +c exp_
x
2
2
+x_
Applying the initial condition y(u) = u gives us c = 1. Therefore,
y(x) = -1 +exp_
x
2
2
+x_
Example 6 Solve
dP
dt
-2tP = P +4t +2
Solution
First we put this in standard form:
JP
Jt
-(2t +1)P = 4t +2
An integrating factor is
c
-](2t+1)dt
= e
-(t
2
+t)

Multiplying by this integrating factor:
(c
-(t
2
+t)
)
JP
Jt
-(c
-(t
2
+t)
)(2t +1)P = (c
-(t
2
+t)
)(4t +2)
Thus,
J
Jt
|c
-(t
2
+t)
P] = c
-(t
2
+t)
(4t +2)
Integrating,
c
-(t
2
+t)
P = _c
-(t
2
+t)
(4t +2)Jt +c
= 2_c
-(t
2
+t)
(2t +1)Jt +c
Evaluating the integral
1

c
-(t
2
+t)
P = -2c
-(t
2
+t)
+c
Solving for P,
P(t) = c e
t
2
+t
-2


1
To evaluate ]c
-(t
2
+t)
(2t +1)Jt, let u = (t
2
+t). Then Ju = (2t +1)Jt and the integral is of the form ]c
-u
Ju =
-c
-u

Copyright Rene Barrientos Page 7

Example 7 Solve the IVP 4
d
dt
+8y = Suexp (-1ut); y(u) = 4u
Solution
The equation in standard form is:
Jy
Jt
+2y =
2S
2
exp (-1ut); y(u) = 4u
Note: as stated earlier, exp(-1ut) = c
-10t
.
An integrating factor of the differential equation is
p = c
]2dt
= c
2t

Applying the integrating factor,
c
2t
Jy
Jt
+2c
2t
y =
2S
2
c
-10t
c
2t

Thus,
J
Jt
(c
2t
y) =
2S
2
c
-8t

We are ready to integrate, but we have a choice; this is an initial value problem, therefore, we either
integrate and then find the arbitrary constant, or we use a definite integral to dispense with that extra step.
Method I: (Use the indefinite integral and then apply the initial conditions)
c
2t
y =
2S
2
_c
- 8t
Jt +c
c
2t
y(t) = -
2S
16
c
- 8t
+c
Apply y(u) = 4u to obtain c = 66S16. Thus,
c
2t
y(t) = -
2S
16
c
- 8t
+
66S
16

Solving for y:
y(t) =
5
1
(133e
-2t
-5e
-1t
)
Method II: (Use the definite integral)
_
J
Js
|c
2s
y(s)
t
0
]Js = _
2S
2
c
- 8s
t
0
Js
Integrating,
c
2t
y(t) -y(u) = -
2S
16
(c
- 8t
-1)
Since y(u) = 4u,
c
2t
y(t) = -
2S
16
c
- 8t
+
66S
16

Hence
y(t) =
5
1
(133e
-2t
-5e
-1t
)
Example 8 Solve the IVP 4tJz -(2t
2
-z)Jt = u; t(1) = S
Solution
Since this equation is given in differential form, we must first decide which variable represents the
independent variable and which one is the dependent. The presence of t
2
tells us immediately that t
cannot be the dependent variable if we are interested in viewing this as a linear equation. Thus, we
choose t to be the independent variable. Then by default z is the dependent variable and the equation can
be written as
Copyright Rene Barrientos Page 8

4t
Jz
Jt
-(2t
2
-z) = u; t(1) = S |Ji:iJing by Jt]
Thus, the general form of the equation is
4t
Jz
Jt
+z = 2t
2
; t(1) = S
You might object to the choice of initial condition; does it not look backwards? But all this condition
says is that the integral curve that we are interested in is the one that has the property that t = 5 when
z = 1, that is, the solution curve contains the point (S,1) in the tz plane.
With this in mind we proceed to put the equation in standard form:
Jz
Jt
+
1
4t
z =
t
2
; z(S) = 1
So that p(t) =
1
4t
We are ready to find the integrating factor:
p(t) = c
][
1
4t
dt
= |t|
14

Note 1: t = u is a singularity of this equation since o
1
(u) = u. Thus, we need avoid intervals containing
the origin.
Note 2: since we are working with initial conditions specified at t = S, we can assume we are working on
an interval in which t > u, say (0,), and dispense with the absolute value. Thus, we can take p(t) =
t
14
is our integrating factor.
t
14
Jz
Jt
+t
14
1
4t
z = t
14

t
2
; z(S) = 1
This simplifies to
t
14
Jz
Jt
+
1
4
t
-34
z =
1
2
t
54
; z(S) = 1
Hence,
J
Jt
(t
14
z) =
1
2
t
54
; z(S) = 1
Integrating,
t
14
z = _
1
2
t
54
Jt +c; z(S) = 1
t
14
z =
1
2

4
9
t
94
+c; z(S) = 1
z =
2
9
t
2
+ct
-14
; t(1) = S
Applying the initial condition,
1 =
2
9
S
2
+c S
-14
=c = -S
14
[
41
9

Substituting for c:
z =
2
9
t
2
-S
14
_
41
9
] t
-14

z(t) =
2
9
t
2
-
41
9
_
5
t
]
1
4

Using the definite integral reduces the amount of work by a few steps. Starting with
J
Jt
(t
14
z) =
1
2
t
54
; z(S) = 1
integrate from the point (S,1) on the t-z plane to some arbitrary point (t, z):
Copyright Rene Barrientos Page 9

_ _r
1
4
z(r)]
i t
5
Jr =
1
2
_ r
54
t
5
Jr
t
1
4
z(t) -S
1
4
z(S) =
1
2

4
9
r
94
|
5
t

t
1
4
z(t) -S
1
4
=
2
9
(t
94
-S
94
)
=
2
9
t
94
-
2
9
S
94

t
1
4
z(t) =
2
9
t
94
-S
1
4

41
9

z(t) =
2
9
t
2
-
41
9
_
5
t
]
1
4

Example 9 Find a solution of the equation
d
dx
= 1(y +x)
Solution
If we take y to be the independent variable, then this equation is not linear. However, there is nothing
special about the variable y and in fact we learn in calculus that
dx
dy
=
1
dydx

provided that JyJx = u.
Thus, the differential equation under consideration may be written as
Jx
Jy
= y +x
which is a linear differential equation whose dependent variable is x. Writing it in standard form,
Jx
Jy
-x = y
An integrating factor is p(y) = c
-
. Thus,
c
-
Jx
Jy
-c
-
x = c
-
y
or
J
Jy
(xc
-
) = c
-
y
Integrating,
xc
-
= _c
-
y Jy +c
Integration by parts gives us
xc
-
= -yc
-
-c
-
+c
Solving for x(y),
x(y) = ce
y
-(y +1)
Example 10 (an application) A large tank contains a 1S-liter mixture in which 1u giams of salt are dissolved.
Salt water of concentration SS gmL enters the tank at a rate of 1 L/min and is quickly mixed. The mixture leaves
the tank at rate of 2 Lmin. (a) How long does it take for the tank to be completely empty? (b) Find the salinity
(measured by the amount of salt per liter of mixture) of the tank at t = S min.
Solution
First we need to derive a mathematical model of how the amount of salt (or whatever chemical is being
considered) changes in the mixture. Let o(t) be the amount of salt in the mixture at time t and let :(t) be
the volume of this mixture.
Copyright Rene Barrientos Page 10


We can summarize the given information in the following figure:











The rate at which salt enters the mixture of leave it is given by the general formula
rate of salt = rate of mixture entering or leaving the tank the concentration of the mixture
If we assume that the mixture is well stirred at all times so that there are no significant variations in
concentration, it is reasonable to assume that the rate at which the amount of salt changes is given by
da
dt
= rate u xa|t |n -rate u xa|t uut
rotc solt in = 1
litcr
min
SS
gm
litcr
= 35
L
m|n

Observe that we obtain the rate at which salt goes in by multiplying the rate at which solution goes in times
the concentration of that solution. Similarly,
rate of salt out = rate of mixture coming out times the concentration of the mixture
The concentration of the solution coming out of the tank is changing in time and is given by
c(t) =
(t)
u(t)

Thus, if we know the volume :(t) of solution in the tank present at any time t, we can obtain an
expression for the concentration of the mixture coming out. We can write a formula for the volume as a
function of time t:
u(t) = u

+(r
|n
-r
uut
) t
Where u

is the initial volume of the mixture in the tank, r


|n
and r
uut
are the rates at which mixture
enters and exist the tank, respectively.
In this example, :
0
= 1S L, r
n
= 1 Lmin and r
out
= 2 Lmin. Therefore the mixtures volume is
changing at a rate of -1 Lmin, that is, it is decreasing by one liter every minute:
u(t) = 15 -t
The concentration in the tank, and also that of the out-flowing mixture, is given by
c(t) =
o(t)
1S -t

Hence, the differential equation governing o(t) is
Jo
Jt
= rotc o solt in -rotc o solt out
= 1
litcr
min
SS
gm
litcr
-2
litcr
min

o(t)
1S -t

litcr
min


Salt water of concentration
SS gmL goes in at a rate
of 1 Lmin
Mixture comes out at a
rate of 2 Lmin
Initially: 1S L,
1u gm. of salt
Copyright Rene Barrientos Page 11

Since the initial amount of salt in the mixture is 1u gm, we have the following initial value problem:

Jo
Jt
= SS -2
o(t)
1S -t
; o(u) = 1u
We are ready to calculate:
(a) from the volume equation, the tank will be empty when :(t) = u, that is, when t = 15 mtn.
(b) To answer the second question, we solve the initial value problem.
Writing it in standard form:

Jo
Jt
+
2
1S -t
o(t) = SS ; A(u) = 1u (o)
An integrating factor for this equation is
p = c
]
2
15-t
dt
= c
-2]
-1
15-t
dt

= c
-2In(15-t)

= (1S -t)
-2

Multiplying (a) by the I.F.
(1S -t)
-2

Jo
Jt
+
2
1S -t
(1S -t)
-2
o(t) = SS(1S -t)
-2

Thus,
J
Jt
((1S -t)
-2
o(t)) = SS(1S -t)
-2

Integrating,
_
J
Jr
((1S -r)
-2
o(r))
t
0
Jr = _ SS(1S -r)
-2
t
0
Jr
(1S -t)
-2
o(t) -(1S)
-2
o(u) = SS_ (1S -r)
-2
t
0
Jr
or
(1S -t)
-2
o(t) -
1u
22S
= -SS_ (1S -r)
-2
t
0
(-1)Jr
(1S -t)
-2
o(t) =
2
4S
+SS_
1
1S -t
-
1
1S
_
(1S -t)
-2
o(t) =
SS
(1S -t)
-
1uS
4S

Solving o(t),
a(t) = 35(15 -t) -
13
45
(15 -t)
2

At t = S, o(S) = 9u.4 gm and :(S) = 12 L. the salinity is approximately 7.53gm/L.